(untitled) (Eurasian Journal of Ecology, 2018)
he article studies the algal flora of Kolsai lakes and provides a biological assessment of their state by the bioindication method. There are 124 species from 6 microalgae divisions were found in the algal flora of investigated lakes. The greatest number of species (72) is recorded in the first Kolsai lake, including diatoms – 41 species, green – 19 species and blue-green – 12. In the composition of second Mynzholka Lake’s algal flora, there are 52 species belonging to four divisions: Bacillariophyta – 24 species, Cyanophyta – 9 species, Chlorophyta – 14 species and Dinophyta – 5 species were identified. The most numerous and diverse in a specific respect are the diatoms (Bacillariophyta), the division is represented by 14 genera and 7 families. In the Upper Kolsai there is a relatively smaller species diversity – 45 species belonging to 5 divisions, 10 classes, 13 orders. At the same time, the largest number of species is also represented by the diatom algae division, totally 31 species were found. It is established that the species richness of Kolsai lakes’ algae varies depending on the location of the studied places, so the algal species’ composition characterized by relatively high diversity in the Lower Kolsai Lake, located at the altitude 1818 m above sea level. Analysis of indicator-saprobic species of Kolsai lakes testify to the absence of signs of contamination in them. Indicators of pure water – oligosaprobes here were the most numerous. The index of saprobity fluctuate within 1.15-1.5, which corresponds to oligosaprobic conditions of the medium. Key words: algal flora of microalgae, bioindication, saprobity index.